Effect of Coagulation Bath Temperature During Preparation of PES Hollow Fiber Supported Liquid Membrane for Acetic Acid Removal - Sathiya, Sanmugam; Norlisa, Harruddin; Syed Mohd Saufi, Tuan Chik (Bangladesh University of Engineering and Technology, 2017)
Acetic acid is a byproduct of acid hydrolysis of biomass during sugar recovery step in biofuel production. Acetic acid can inhibit the enzyme used during fermentation of sugar to the ethanol. Hollow fiber supported liquid membrane (SLM) was used in this study to remove acetic acid from aqueous solution. Liquid membrane was formulated using trioctylamine and 2-ethyl hexanol as a carrier and solvent, respectively. The hollow fiber membrane support was prepared from 15 wt.% polyethersulfone, 42.5 wt.% polyethyleneglycol 200 and 42.5 wt.% dimethylacetamide. The effect of coagulation bath temperature (CBT) at 30ºC, 40ºC and 50ºC during hollow fiber membrane spinning process was investigated. The porosity of the membrane increased as the CBT increased. The porosity of the membrane prepared using CBT of 30ºC, 40ºC and 50ºC were 35.7%, 46.7% and 61.6%, respectively. SLM process using hollow fiber membrane prepared at 50ºC of coagulation bath was able to remove 52% of acetic acid from the aqueous solution.